Development of model of efficiency of activity of machine-building enterprises - G. I. Kolke; N. A. Kalaytan (Вестник СибАДИ, 2017)
In article analyze features of activity of the enterprises of mechanical engineering are reflected. It is noted that in increase of efficiency of activity of the enterprises plays intra firm planning of production resources huge role. The assessment of efficiency of activity of the enterprise becomes complicated in the conditions of deficiency of production resources and influence internal and environment. Considering features of the activity of the enterprises of mechanical engineering representing sequence of business processes the efficiency assessment model, as separate process, and in general the enterprise is offered.